KAJIAN PENERAPAN PRINSIP PRODUKSI BERSIH PADA PROSES MANUFAKTUR PIPA APUNG - wahyu purwanta (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Manufacture process of floating hose is a rubber technical commodity process, which has potencies to pollute the environment. Two types of waste, which are produced from the purification process and rubber latex process, are liquid and solid waste. Beside those waste, the component developing process, which uses several chemical agents, also has negative impacts to the human who has intensive contacts with those chemicals. Calendering and vulcanisation process are also produce air pollutants, especially the contaminated air from some harmful parameters. Considering that floating hose product will be used by oil companies with very high technical specification, it is necessary to prepare an environmental friendly material and construction technic. Those eco-efficiency planning should bearranged since the beginning, from the using of energy and water resources until waste management and disposal and good house keeping. All materials should be choosen with environmental approach and 4R principle (reduce, reuse, recovery and recycle) must be used for waste disposal activity.